Anti-metastatic Activity of Curcumin Analog Pentagamaboronon-0-Sorbitol Against HER2-overexpressed MCF-7 Breast Cancer Cells - Lailatul Qodria; Indah Hairunisa; Rohmad Yudi Utomo; Adam Hermawan; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2018)
Breast cancer with Human Epidermal Growth Factor Receptor (HER)2 overexpression increases tumor progession and lead to metastasis, which is primarily cause of mortality in breast cancer. Pentagamaboronon-0 Sorbitol (PGB-0-So) is an aquoeous formulation of curcumin analog, PGB-0, with sorbitol. This compound has been developed as an anti-cancer chemotherapeutic agent and a boron carrying pharmaceutical for boron neutron capture therapy (BNCT). The aims of this study are to investigate antimetastatic activities of PGB-0-So against HER2-overexpressed MCF-7 breast cancer (MCF-7/HER2) cells. The MTT cytotoxicity assay of PGB-0-So exhibited cytotoxic effect with an IC50 value of 35 μM. The testing of anti-migration activity using the scratch wound healing assay demonstrated that PGB-0-So inhibited the closure of the wound on MCF-7/HER2 cells compare to the control. Furthermore, PGB-0-So was able to suppress matrix metalloproteinase (MMP)-9 activities, based on the gelatin zymography assay. In conclusion, PGB-0-So has potency to be developed as an anti-cancer agent against metastatic breast cancer.Keywords : PGB-0-So, anti-metastatsis, cell migration, MMP-9, MCF-7/HER2